2005
DOI: 10.1148/radiol.2361040148
|View full text |Cite
|
Sign up to set email alerts
|

Aortoiliac Occlusive Disease in Patients with Known or Suspected Peripheral Vascular Disease: Safety and Efficacy of Gadofosveset-enhanced MR Angiography—Multicenter Comparative Phase III Study

Abstract: On the basis of substantial improvements over non-contrast MR angiography in efficacy and a minimal and transient side-effect profile, gadofosveset was found to be safe and effective for MR angiography in patients known or suspected to have peripheral vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 24 publications
3
47
0
1
Order By: Relevance
“…These findings demonstrate that CE-MRA overcame some intrinsic limitations associated with noncontrast MRA in complex, tortuous, or turbulent flow vessels, such as diseased aortoiliac arteries and are consistent with those reported from another multicenter study (13). In this study we sought to answer two main questions: 1) Does CE-MRA improve the ability to diagnose aortoiliac stenoses compared with noncontrast enhanced MRA?…”
Section: Discussionsupporting
confidence: 75%
“…These findings demonstrate that CE-MRA overcame some intrinsic limitations associated with noncontrast MRA in complex, tortuous, or turbulent flow vessels, such as diseased aortoiliac arteries and are consistent with those reported from another multicenter study (13). In this study we sought to answer two main questions: 1) Does CE-MRA improve the ability to diagnose aortoiliac stenoses compared with noncontrast enhanced MRA?…”
Section: Discussionsupporting
confidence: 75%
“…9 In our experience, inner-thigh and midsection burning and discomfort, sometimes described on more rapid injection of BPA, are mitigated by the slower injection rate prescribed in our studies. 21 Frydrychowicz et al 13 estimated both SNR and contrast-tonoise ratio (CNR) between SCA and BPA; however as they point out, and as thoroughly expounded previously by Reeder et al, 22 SNR and CNR measurements of multichannel receive datasets are not straightforward, given the spatial nonuniformity of noise amplification inherent to parallel acceleration. For this reason, we believe qualitative estimates of image quality and quantitative descriptions of contrast kinetics to be more relevant to clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have demonstrated its safety. In phase III trials of Ablavar performing MR angiography of the aortoiliac region in adults patients with known or suspected to have peripheral vascular disease, the most common adverse events were feeling hot (4.4%), nausea (3.6%), headache (3.3%) and burning sensation (2.9%); the incidence of severe and serious adverse events was low (19,20). Of note, QTc prolongation has been reported following gadofosveset administration, and therefore patients should be assessed for a history of underlying conditions that may predispose to arrhythmias from QTc prolongation.…”
Section: Contrast Agentsmentioning
confidence: 99%